Wonder what else is wonderful - Abd Razak, Dzulkifli (2007)
THE world now has a new set of "world wonders" based on over 100 million votes cast by people in 200 countries. The socalled New Seven Wonders of the World, declared in Lisbon on July 7, included two sites in Asia— the Great Wall of China and the Taj Mahal in India. The list, drawn from 21 shortlisted contenders, had been controversial from the start. It attracted criticism even from the United Nations Educational, Scientific and Cultural Organisation (Unesco), which said the new wonders should not be chosen in a popular vote. Others cited it as being flawed since multiple votes were allowed, presumably not much different from how fans and diehards vote for their idols in reality shows.